2023
DOI: 10.3390/diagnostics13061091
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as a Potential Biomarker in the COVID-19 Infection and Complications Course, Severity, and Outcome

Abstract: During the last three years, since the emergence of the COVID-19 pandemic, a significant number of scientific publications have focused on resolving susceptibility to the infection, as well as the course of the disease and potential long-term complications. COVID-19 is widely considered as a multisystem disease and a variety of socioeconomic, medical, and genetic/epigenetic factors may contribute to the disease severity and outcome. Furthermore, the SARS-COV-2 infection may trigger pathological processes and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 125 publications
0
1
0
Order By: Relevance
“…Our results further highlight the importance of long non-coding RNAs [32] and microR-NAs [33] as emerging regulators in SARS-CoV-2 infection. Patients with ARDS at baseline presented higher levels of CLRN1-AS1, a lncRNA that inactivates the Wnt/β-catenin signaling pathway [34], and IRAIN, which enhances the formation of an intrachromosomal promoter loop of IGF1R [35].…”
Section: Discussionsupporting
confidence: 55%
“…Our results further highlight the importance of long non-coding RNAs [32] and microR-NAs [33] as emerging regulators in SARS-CoV-2 infection. Patients with ARDS at baseline presented higher levels of CLRN1-AS1, a lncRNA that inactivates the Wnt/β-catenin signaling pathway [34], and IRAIN, which enhances the formation of an intrachromosomal promoter loop of IGF1R [35].…”
Section: Discussionsupporting
confidence: 55%
“…miRNAs play crucial roles in gene expression regulation. Several studies have explored the association between specific miRNAs and factors including prognosis, prediction of disease severity, and complications in patients who have recovered from COVID-19 [ 54 ]. Specific miRNAs have been found to correlate with the severity of lung injury and the development of post-COVID-19 pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews found elevated levels of inflammatory biomarkers and cytokines, such as C reactive protein (CRP), IL-6, D-dimer, lactate dehydrogenase (LDH) and TNF-α in people with long-COVID [67,122]. Furthermore, in the context of epigenetic changes, miRNA regulation during different stages of acute SARS-CoV-2 infection demonstrated its potential to help in patient stratification allowing for the estimation of heightened risk of long-term health issues following the acute phase [123]. These miRNA profiles also hold promise for identifying informative biomarkers that can be targeted for preventive measures.…”
Section: Epigenetic Influence On Long-covidmentioning
confidence: 99%